Spectrophotometric analysis evaluating apical microleakage in retrograde filling using GIC, MTA and biodentine: an in-vitro study - Manisha Nepal; Snigdha Shubham; Rupam Tripathi; Jwolan Khadka; Deepa Kunwar; Vanita Gautam; Narayan Gautam (BMC, 2020)
Abstract Background The present study compares the apical microleakage of three different root-end filling materials in which the retrograde cavity is prepared by two different burs. Methods Eighty extracted single rooted maxillary and mandibular premolars were taken. Root canal treatment was completed. Apical 3 mm of all the teeth were resected with diamond disk. The tooth were divided into four groups with two subgroups for each group containing 10 tooth (N = 10) as: Group IA (Negative Control and IB (Positive Control); Group IIA and IIB: Prepared with round carbide bur and round diamond bur respectively, filled with GIC; Group IIIA and IIIB: Prepared with round carbide bur and round diamond bur respectively, filled with MTA; Group IVA and IVB: Prepared with round carbide bur and round diamond bur, filled with Biodentine. After applying two coats of nail varnish leaving apical 3 mm (except for negative control group) all teeth were immersed in 2% methylene blue for 3 days and again in 65% nitric acid for next 3 days for extraction of dye. The obtained solution was then transferred to eppendorf tube and centrifuged in microcentrifuges at 14,000 revolution per minutes (RPM) for 5 min. Optical density or absorbance of the supernatant solution was measured with UV spectrophotometer at 550 nm. Results The absorbance of the supernatant solution after dye extraction is decreasing in the order of positive control> GIC > MTA > Biodentine> negative control group. The significant difference was observed between GIC and MTA (p = 0.0001) and GIC and Biodentine (p = 0.0001) with two different burs but statistically non-significant difference was observed between MTA and Biodentine with Carbide bur (p = 0.127) and Diamond bur (p = 0.496) respectively. Conclusions Within the limitations of the present study, it can be concluded that Biodentine and MTA showed less microleakage as compared to GIC. There is no significant difference between mean microleakage of MTA and Biodentine. However, the mean OD of the Biodentine was least of all evaluated materials. Preparation of the root-end using round carbide bur as well as round diamond burs showed comparable microleakage for all three filling materials.